Microaspiration Syndrome in Pediatric Practice: Modern Features and Role in Bronchial Obstruction Syndrome Formation - S.I. Ilchenko; E.D. Duka; L.A. Zhukova (Zaslavsky O.Yu., 2016)
The paper presents the data on research of aspiration syndrome prevalence among young children treated in the City children's pulmonary department due to protracted course of obstructive bronchitis. The structure of microaspiration reasons in young children was studied (2010-2015). The most significant reasons of microaspiration syndrome development were revealed depending on children age. Modified questionnaire for the parents was used to collect anamnesis effectively. The children with perinatal impairment of nervous system, preterm children, and the children with morphological and physiological nasopharyngeal defects, with muscular dystonia are firstly in risk group for microaspiration syndrome. Microaspiration may manifest with frequent regurgitation, vomiting during cough, meal leaking from the nose, correlation of coughing fit with feeding, exacerbation or development of coughing in prone position, fit of night coughing and asphyxia, long-term hacking after cough attack. Pediatricians are recommended to observe attentively their patients during each feeding as dysphagy could be inconstant. Microaspiration syndrome is a challenging for diagnosis and requires complex approach, as mostly diagnostic procedures are invasive. Timely diagnosis and treatment of microaaspiration syndrome allow decrease respiratory diseases rate in young children and reduce obstructive bronchitis duration.